Cyberspace As a Platform of Social Impact - Grzegorz PILARSKI; Maciej MARCZYK (Communications of International Proceedings, 2021)
The article presents certain aspects of using cyberspace as a perfect platform of social impact, used with regard to hybrid threats and hybrid warfare in particular. The authors made an attempt to answer the following question: ‘To what extent can cyberspace become an element of social impact with regard to hybrid warfare?’ Presently, cyberspace is used more and more often as a convenient platform to initiate hybrid threats, which might have direct implications for the security of the state and the people. The research problem concerns the assessment of the use of cyberspace as a platform of social impact during hybrid warfare. The analysis of the available factographic sources allowed to identify the areas of cyberspace being the element of social impact. Using cyberspace as a trigger point for hybrid threats, and hybrid warfare in particular, provides potentially big possibilities of social impact not only through social media but also through the possibility of anonymous communication as well as exerting influence on the state critical infrastructure.
Keywords: Cyberspace; Hybrid Warfare; social media; Hybrid Threats.